A multimodal deep learning-based model for posture asymmetry recognition and sports injury risk prediction in adolescent table tennis athletes - Wang, D.; Guo, Y. (Frontiers in Physiology, 2026)
Background: Adolescent table tennis athletes face significant sports injury risks due to repetitive unilateral force generation patterns during the critical skeletal maturation period, yet traditional posture assessment methods lack quantitative precision and real-time monitoring capability.